Does clinical training period support patient-centeredness perceptions of medical students?. Issue 1 (1st January 2019) - Alimoglu, Mustafa Kemal; Alparslan, Derya; Daloglu, Mustafa; Mamakli, Sumer; Ozgonul, Levent
ABSTRACT: Background : Learning environment influences students' professional formation and patient-centered attitudes and behaviors. Objective : The purpose of this study is to investigate how hidden curriculum of learning environment and the previous experience with chronically ill patients affect patient-centeredness perceptions of medical students. Design : We followed 144 students and determined their opinions on 'ideal patient-centered practice and learning environment' via patient-centeredness questionnaire (PCQ) just before (third year) and at the end (sixth year) of clinical training years of medical school. At the end of each clinical training year (fourth, fifth, and sixth years), we determined experiences of the students about 'patient-centeredness of the learning environment' using a relevant survey called communication, curriculum, and culture (C3) instrument. We also compared PCQ and C3 instrument scores of the participants who had chronically ill patient in their families/friends and who do not. Results : C3 scores worsened over the years, namely, students faced increasing number of examples against patient centeredness. Final PCQ scores were worse than initial ones. C3 and PCQ scores of the students who had previous experience with chronically ill patients were not different from the scores of the remaining students. Conclusion : Medical students, even those who have a chronically ill patient in their families or friends, lose their idealism about patient centeredness to some degree possibly due to hidden curriculum of the medical school.